2019
DOI: 10.3390/en12091659
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Inversion of Fixed Carbon Content in Coal Gangue by Thermal Infrared Spectral Data

Abstract: Fixed carbon content is an important factor in measuring the carbon content of gangue, which is important for monitoring the spontaneous combustion of gangue and reusing coal gangue resources. Although traditional measurement methods of fixed carbon content, such as chemical tests, can achieve high accuracy, meeting the actual needs of mines via these tests is difficult because the measurement process is time consuming and costly and requires professional input. In this paper, we obtained the thermal infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…This showed that the hydroxyl structure in mechanically activated coal gangue decreases and the amount of adsorbed water increases with the increase in grinding time. (2) The peaks at 940 cm −1 and 913 cm −1 belong to the bending vibration of inner surface hydroxyl and inner hydroxyl, respectively [40,42]. With the increase in mechanical grinding time, the two peaks gradually weakened and disappeared at 20 h, which further confirmed the removal of the hydroxyl structure in mechanically activated coal gangue.…”
Section: Effect Of Mechanical Activation On Coal Gangue Structurementioning
confidence: 78%
See 2 more Smart Citations
“…This showed that the hydroxyl structure in mechanically activated coal gangue decreases and the amount of adsorbed water increases with the increase in grinding time. (2) The peaks at 940 cm −1 and 913 cm −1 belong to the bending vibration of inner surface hydroxyl and inner hydroxyl, respectively [40,42]. With the increase in mechanical grinding time, the two peaks gradually weakened and disappeared at 20 h, which further confirmed the removal of the hydroxyl structure in mechanically activated coal gangue.…”
Section: Effect Of Mechanical Activation On Coal Gangue Structurementioning
confidence: 78%
“…According to the XRD spectra of raw coal gangue and mechanically activated coal gangue: (1) The intensity of the diffraction peaks at 12.46 • , 24.99 • , 35.11 • , and 38.55 • associated with the kaolinite structure decreased significantly after grinding for 2 h, became very weak after grinding for 10 h, and disappeared completely after grinding for 20 h. The intensity reduction of the kaolinite structure indicated that the stable crystal structure of kaolinite in coal gangue can be effectively destroyed by mechanical grinding. (2) The intensity of the diffraction peaks of muscovite at 8.94 • and calcite at 29.5 • weakened at 2 h grinding and disappeared at 10 h grinding, indicating that the structures of muscovite and calcite were also destroyed. (3) The diffraction peaks of quartz at 20.96 • and 26.73 • were stable during the mechanical grinding process and the peak intensities were always significant, which showed that the quartz structure in coal gangue is stable.…”
Section: Effect Of Mechanical Activation On Coal Gangue Structurementioning
confidence: 97%
See 1 more Smart Citation
“…Coal gangue is the main solid waste generated during coal mining and washing, accounting for about 10-25% of total coal production [1][2][3][4]. With the progress of coal mining activities, coal gangue accumulates in large quantities; it has become one of the largest industrial residues [5,6]. The accumulation of coal gangue not only occupies large land resources but also causes serious environmental problems, such as soil pollution, soil degradation, geological disasters, and air pollution [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%